Pengaruh Penggunaan Media Pembelajaran Microsoft Powerpoint dan Wordwall Terhadap Hasil Belajar Peserta Didik Pada Materi Statistika Kelas X di SMAN Ngoro - Nurfaiza, Dia nita; Iesyah Rodliyah (Discovery, 2025)
This study aims to describe whether or not there is an impact of the application of Wordwall media and Microsoft PowerPoint on the learning of statistics of class X students, and to observe the magnitude of its contribution. The study was conducted by SMAN Ngoro with subjects X-6 and X-7. This study uses quantitative techniques, from the form of quasi-experiments. The results show that both media can significantly increase students' mathematics learning outcomes. Given the fact that the application of both increases the average student learning outcomes. From the hypothesis test, it was found that sig (2-tailed) 0.000 or (0.000 <0.05, meaning H0 is rejected and H1 is accepted, indicating that there is a comparison between classes with the application of both media and classes with conventional techniques. Then the effect size produced was around 1.6, which is considered high or 94.5%. It can be interpreted that the application of both media contributes to student learning outcomes.